2017
DOI: 10.1103/physreva.95.031801
|View full text |Cite
|
Sign up to set email alerts
|

Collapse events of two-color optical beams

Abstract: In this work, we study optical self-focusing that leads to collapse events for the time-independent model of co-propagating beams with different wavelengths. We show that collapse events depend on the combined critical power of two beams for both fundamental, vortex and mixed configurations as well as on the ratio of their individual powers

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Third, by engineering the initial phases of the seed components, the maximum intensity can be optimized for the same efficiency. Additionally, following the recent study that found that the total critical intensity for selffocusing might be higher for multicolor beams [40], we expect to find a similar delay in the transverse filamentation instability since the same nonlinear Kerr term is responsible for both effects. Such a delay might enable longer amplification before encountering this transverse instability, making MFBRA even more favorable over SF-BRA.…”
Section: Discussionsupporting
confidence: 62%
“…Third, by engineering the initial phases of the seed components, the maximum intensity can be optimized for the same efficiency. Additionally, following the recent study that found that the total critical intensity for selffocusing might be higher for multicolor beams [40], we expect to find a similar delay in the transverse filamentation instability since the same nonlinear Kerr term is responsible for both effects. Such a delay might enable longer amplification before encountering this transverse instability, making MFBRA even more favorable over SF-BRA.…”
Section: Discussionsupporting
confidence: 62%
“…From the linear stability analysis of the system Eqs. (40,41) we obtain that always one of the linear equilibrium solutions is asymptotically stable, and the second always unstable. This fact however, does not guarantee the nonlinear stability of the system all together.…”
Section: Radial Limiting Modementioning
confidence: 69%
“…which has the so-called Townes modes as pulses solutions, if 2σ ≤ 2, [33]. The Townes modes can become stable solitons, [40], in the case of self-focusing NLS solution collapse and if their energy is smaller than the critical energy 2π ∞ 0 rT 2 (r)dr, [33]. In our case, Eq.…”
Section: Spiral Solutions In the Quadratic Approximationmentioning
confidence: 71%
See 2 more Smart Citations